Are Pediatric Emergency Care Applied Research Network Rules (PECARN) Sufficient for Computed Cranial Tomography Decision in Pediatric Patients with Mild Head Trauma?. Issue 1 (2016) - Durgun, Hasan Mansur; Tektaş, Erkan; Zengin, Yılmaz; Dursun, Recep; İçer, Mustafa and Üstündağ, Mehmet and Orak, Murat and Güloğlu, Cahfer
No abstract available